Manajemen Laba Dan Pengaruhnya Pada Kinerja Perusahaan Yang Melakukan Penawaran Saham Tambahan - Dewi, Gusti Ayu Made Sari; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 12 No 2 (2015), 2015)
The purpose of this study was to examine earnings management in companies that do offer additional shares. Data analysis techniques used are two different test average. Test results discretionary accruals with Modified Jones Model shows that discretionary accruals prior to the implementation of additional stock offering higher than the post-implementation offers additional shares. Real earnings management activity by proxy abnormal operating cash flow and abnormal production costs showed results that abnormal operati ng cash flow two years prior to the implementation of additional stock offering lower than two years after the offering of additional shares and abnormal production costs one year prior to the implementation of additional stock offerings more higher compared with one year after the offering of additional shares. This study that discretionary accruals two years prior to the implementation of additional stock offerings impact on the financial performance of the company after dilaksanakanya additional stock offering. The implication of this research is to be more investors seeking information about the company not only through financial statements presented by the management company
Keywords: seasoned equity offering, discretionary accruals,real managemet